PEMANFAATAN INFRASTRUKTUR DAN RUANG PASCA PEMBANGUNAN INFRASTRUKTUR DI DESA KERTA, PAYANGAN, GIANYAR - Desak Putu Korpiyoni (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2021)
Indonesia consists of urban areas and rural areas. The problems also can be find it’s not only urban areas have many problems, in rural areas have many problems too. Some problems in rural areas which is not complete is lack of infrastructure, which is to support accessibility and productivity distribution of agriculture product, and it has been hampering economic growth in rural areas. In several things needed for support villagers agriculture activities in rural area is design of infrastructure should be compatible with society and public needs in rural area, other than that, the potential in rural area can be visible. Kerta Village located in Payangan District, Gianyar Regency. The consideration of Kerta Village was chosen as an object of research because infrastructure built with massive and followed with space development during six years clearly visible so that until now village tourism has been built. It need requires an analysis can planning and development according to the needs of Kerta Villagers. The objective of this research is to discover the impact of the planning and development of infrastructure in Kerta Village. This research used qualitative method with case study approach. The result of the research is the analysis of planning and development infrastructure in Kerta Village during six years started 2014 until 2019 and also space utilization since the infrastructure development in Kerta Village.